2019
DOI: 10.3389/fonc.2019.01314
|View full text |Cite
|
Sign up to set email alerts
|

An Immune-Related Signature Predicts Survival in Patients With Lung Adenocarcinoma

Abstract: We investigated the local immune status and its prognostic value in lung adenocarcinoma. In total, 513 lung adenocarcinoma samples from TCGA and ImmPort databases were collected and analyzed. The R package coxph was employed to mine immune-related genes that were significant prognostic indicators using both univariate and multivariate analyses. The R software package glmnet was then used for Lasso Cox regression analysis, and a prognosis prediction model was constructed for lung adenocarcinoma; clusterProfiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 37 publications
1
99
4
Order By: Relevance
“…Recently pro les of 14 IRGs in lung adenocarcinoma that showed high prediction accuracy and stability in identifying immune features [42]. Our research differed from previous studies in several ways.…”
Section: Discussioncontrasting
confidence: 81%
“…Recently pro les of 14 IRGs in lung adenocarcinoma that showed high prediction accuracy and stability in identifying immune features [42]. Our research differed from previous studies in several ways.…”
Section: Discussioncontrasting
confidence: 81%
“…The AUC for 1-and 3-year of the immune signature in training cohort was 0.70 and 0.68, respectively, and in validation cohort was 0.72 and 0.73, respectively, all of which were inferior to that in this study. Similarly, a study reported an immune-related signature [17], which AUC of 1-(0.78) and 3-(0.76) year was also lower than that of this study. In addition, Zhang et al constructed a glycolysis-related gene prognostic signature with the AUC = 0.72 [18].…”
Section: Discussioncontrasting
confidence: 65%
“…This analysis involved data from 192 1p19q codeletion LGG samples and 394 non-deletion LGG samples. 1p19q co-deletion associated immune-related DEGs were identi ed from the DEGs based on immune-related gene annotation on the IMMPORT website (https://www.immport.org/) [11]. Only genes shared by CGGA and TCGA were included in downstream analyses.…”
Section: Identi Cation Of Immune-related Genes Correlated With 1p19qmentioning
confidence: 99%